Pharmacological relevance of taraxasterol: A review - Olabisi Tajudeen Obafemi; Ademola Olabode Ayeleso; Blessing Ariyo Obafemi; Olusola Bolaji Adewale; Benjamin Olusola Omiyale; Sogolo Lucky Lebelo; Monde McMillan Ntwasa (Pharmacological Research - Modern Chinese Medicine)
Introduction: Taraxasterol is a pentacyclic triterpenoid which was first discovered from the roots of Taraxacum officinale. However, it is generally found in the Taraxacum genus (Pugongying in Chinese). It has been reported to possess several medicinal properties, and modulate several biochemical and metabolic signaling pathways as a means of exerting its pharmacological effects. Even though some biological effects have been ascribed to taraxasterol, it is still being explored for more therapeutic benefits. This review aimed to highlight the relevance of taraxasterol as an antidiabetic, anti-cancer, anti-inflammatory and an antioxidant agent. Methods: Articles for this review were searched on Scopus, Nature, SpringerLink and PubMed databases. The keywords used for the search were “taraxasterol pharmacology”, “taraxasterol antioxidant”, “taraxasterol cancer”, “taraxasterol biosynthesis” and “taraxasterol antidiabetic”. Relevance and report of distinct mechanisms of action were considered in the selection. Results: This review underlines the therapeutic potential of taraxasterol in cancer and diabetes conditions, while also highlighting its anti-inflammatory and antioxidant effects. Some specific biochemical pathways that are modulated due to the pharmacological effect of taraxasterol were diagrammatically represented. Conclusions: It is hoped that this review would stimulate interest in taraxasterol by focusing on its pharmacological relevance, specific mechanisms of action and pharmacokinetics. This might facilitate its eventual development into drug and adoption into treatment regimen of various diseases.